Asthma at 8 years of age in children born by caesarean section. Issue 2 (3rd December 2008) - Roduit, C; Scholtens, S; de Jongste, J C; Wijga, A H; Gerritsen, J; Postma, D S; Brunekreef, B; Hoekstra, M O; Aalberse, R; Smit, H A
Abstract : Background: Caesarean section might be a risk factor for asthma because of delayed microbial colonisation, but the association remains controversial. A study was undertaken to investigate prospectively whether children born by caesarean section are more at risk of having asthma in childhood and sensitisation at the age of 8 years, taking into account the allergic status of the parents. Methods: 2917 children who participated in a birth cohort study were followed for 8 years. The definition of asthma included wheeze, dyspnoea and prescription of inhaled steroids. In a subgroup (n = 1454), serum IgE antibodies for inhalant and food allergens were measured at 8 years. Results: In the total study population, 12.4% (n = 362) of the children had asthma at the age of 8 years. Caesarean section, with a total prevalence of 8.5%, was associated with an increased risk of asthma (OR 1.79; 95% CI 1.27 to 2.51). This association was stronger among predisposed children (with two allergic parents: OR 2.91; 95% CI 1.20 to 7.05; with only one: OR 1.86; 95% CI 1.12 to 3.09) than in children with non-allergic parents (OR 1.36; 95% CI 0.77 to 2.42). The association between caesarean section and sensitisation at the age of 8 years was significant only in children of non-allergic parents (OR 2.14; 95% CI 1.16 to 3.98). Conclusions: Children born by caesarean section have a higher risk of asthma than those born by vaginal delivery, particularly children of allergic parents. Caesarean section increases the risk for sensitisation to common allergens in children with non-allergic parents only.